The Relationship Between Screen Time and Emotional Regulation In Children Aged 5–6 Years - Ach Suryansyah Maulana Soleh; Yes Mathoes Lasarus Malaikosa; Mallevi Agustin Ningrum (Journal of Islamic Education Students (JIES), 2026)
Emotional regulation is a central component of early childhood development, particularly for children aged 5–6 years who are transitioning toward formal schooling. Recent advances in digital technology have substantially increased young children’s exposure to screen-based media, commonly referred to as screen time, prompting concerns about its implications for emotional development. This study examines the relationship between screen time and emotional regulation among children aged 5–6 years using a quantitative correlational design. Participants included children aged 5–6 years, with parents and classroom teachers serving as respondents. Screen time data were collected through parent-reported questionnaires, while emotional regulation was assessed via teacher questionnaires and structured observations. Correlational analyses revealed a significant association between screen time and emotional regulation: higher and poorly regulated screen time exposure was linked to lower levels of emotional regulation. These findings underscore the importance of intentional adult supervision and balanced digital media management to support healthy emotional development in early childhood.